Raman imaging of carbon-based nano-materials and development of near-field Raman imaging techniques - You, Yu Meng (2010)
After decade’s development, Raman spectroscopy is now one of the routine spectral tools for its non-destructive, minimum sample preparation and capabilities in probing the information of the crystalline order, chemical composition, strain/stress, temperature and even electronic properties. With the help of the development of the microscopic instrument, the sensitivity and precision of Raman spectroscopy receive great improvement. This thesis is devoted to two aspects of the Raman spectroscopy: 1). the improvement of the Raman spectroscopy featuring researches on the advanced Raman spectroscopy/imaging techniques; 2). the application of Raman spectroscopic studies on the rapid developing carbon-based nano-materials, e.g. carbon nanotubes and graphene.